2017
DOI: 10.1039/c6bm00921b
|View full text |Cite
|
Sign up to set email alerts
|

Personalized protein corona on nanoparticles and its clinical implications

Abstract: It is now well understood that once in contact with biological fluids, nanoscale objects lose their original identity and acquire a new biological character, referred to as a protein corona. The protein corona changes many of the physicochemical properties of nanoparticles, including size, surface charge, and aggregation state. These changes, in turn, affect the biological fate of nanoparticles, including their pharmacokinetics, biodistribution, and therapeutic efficacy. It is progressively being accepted that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
204
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 242 publications
(214 citation statements)
references
References 85 publications
0
204
0
Order By: Relevance
“…Based on the fact that nanoscale objects acquire a protein corona in presence of biological fluids [3], Hajipour et al designed a colorimetric technique for the detection and discrimination of Alzheimer's disease (AD) and multiple sclerosis (MS). The authors first generated a system containing gold nanoparticles (AuNPs) coated with citrate [4].…”
Section: Multicolor Barcoding Of Cells For Long-term Tracking In Vitrmentioning
confidence: 99%
“…Based on the fact that nanoscale objects acquire a protein corona in presence of biological fluids [3], Hajipour et al designed a colorimetric technique for the detection and discrimination of Alzheimer's disease (AD) and multiple sclerosis (MS). The authors first generated a system containing gold nanoparticles (AuNPs) coated with citrate [4].…”
Section: Multicolor Barcoding Of Cells For Long-term Tracking In Vitrmentioning
confidence: 99%
“…Not only external factors like temperature, ionic strength, protein concentration and fluid composition, but also characteristics of the patient such as gender, pathology, age, background and lifestyle strongly influence the PC composition. 22 Since the PC affects the properties of the NP surface, it has significant impact on the interaction between membrane and NPs. [23][24][25][26][27] Many studies are described in the literature where NP cellular uptake is related to the presence of a PC on the NPs in biological fluids, [28][29][30] in particular it has been shown that a key factor in NPs cellular uptake is their adhesion to the cell membrane that significantly affects their final uptake rates.…”
Section: Introductionmentioning
confidence: 99%
“…This has led to some inconsistencies among findings, including: (1) the considerable variability in the protein corona formed on the same nanoparticle; (2) a substantial gap between in vitro and in vivo readouts; (3) differences between therapeutic and targeting efficacies of the same nanoparticles in different media; and (4) unsuccessful clinical outcomes of nanoparticles with positive in vitro and in vivo outcomes. This may be one of the main reasons why, despite numerous advances in nanomedicine, few nanoparticles have reached clinical trials, and even fewer have reached clinical practice 94,132 .…”
Section: Challenges In Designing Nanoparticles For Clinical Applicationsmentioning
confidence: 99%
“…In addition to mass production of similar nanoparticles, the personalized biological identity of nanoparticles (that is, an individual’s protein corona) can significantly affect their efficacy and possible cardiotoxicity 132 . Recent developments in the field of nano-bio interactions have revealed that different types of disease may change the biological identity—and thus the efficacy—of the same nanoparticles 131,143 .…”
Section: Conclusion and Future Challengesmentioning
confidence: 99%